Evaluation of Fire Protection Systems in Hotel Building (Case Study: Grand Kanaya Hotel Medan) (International Journal of Architecture and Urbanism, 2020)
Hotel is a public living facility for tourists by providing room services, food and beverage providers, and accommodation with payment terms. Fire is a flame, both small and large, which is usually hard to control and detrimental and can occur in a place that we do not expect. Ensuring the protection of hotel residents is one of the goals of hotel business standards. Grand Kanaya Hotel is a 3-star hotel building in the city of Medan, with 152 units of rooms and several facilities that enable activities involving large numbers of people, such as restaurants and ballrooms. According to the quite high number of occupants, Grand Kanaya Hotel requires a fire protection system that can protect all hotel residents against fire hazards. The study aims to evaluate the fire protection system that has been applied to the building of the Grand Kanaya Hotel and provide references for fire protection systems that are standard in hotel buildings. This research is using the qualitative method that obtains from field observation and uses a type of descriptive research that explains the facts or existing conditions of fire protection systems in the Grand Kanaya Hotel building. The results show that there are several fire protection systems in Grand Kanaya Hotels that not according to the standards, such as the minimum size, the material used is not resistant to fire, and maximum distance lies, which still exceeds the maximum value. The study results are useful as information for other researchers and hotels regarding fire protection systems at the Grand Kanaya Hotel building.